Stable and reusable calcium-responsive biopolymer for affinity precipitation of therapeutic antibodies - Park, Heesun; Oh, Jeong-Seok; Lee, Jonghwan; Bang, Jinho; Park, Keunwan; Jeong, Suhyeon; Park, Seho; Woo, Jae-Sung; Kim, Sunghyun (Cold Spring Harbor Laboratory Press, 2024)
Affinity precipitation is an attractive method for protein purification due to its many advantages, including the rapid capture of target proteins, simple processing, high specificity, and ease of scale-up. We previously reported a robust antibody purification method using Ca2+-dependent precipitation of ZZ-hCSQ2, a fusion protein of human calsequestrin 2, and the antibody-binding protein ZZ. However, the stability of this fusion protein was not sufficiently high for industrial use because the antibody recovery yield decreased to 60% after being reused 10 times. To identify a more stable calsequestrin (CSQ), we calculated Rosetta energy values for the folding stabilities of various CSQ homologs and selected human CSQ1 (hCSQ1) with lowest energy value (-992.6) as the new CSQ platform. We also identified that the linker sequence between ZZ and CSQ was vulnerable to proteases and alkaline pH by N-terminal protein sequencing. Therefore, we changed the linker to four asparagine (4N) sequences, which were shorter and less flexible than the previous glycine-rich linker. The new version of ZZ-CSQ, ZZ-4N-hCSQ1, was stable in a protease-containing conditioned medium obtained from the cultured Chinese hamster ovary cell or high pH condition (0.1M sodium hydroxide) for more than 5 days and could be reused at least 25 times for antibody purification without loss of recovery yield. The antibodies purified by ZZ-4N-hCSQ1 precipitation also showed greater purity (similar to 33.6-fold lower host cell DNA and similar to 6.4-fold lower host cell protein) than those purified by protein A chromatography. These data suggest that ZZ-4N-hCSQ1 precipitation is more efficient and can achieve cost-effectiveness of up to 12.5-fold cheaper than previous antibody purification methods and can lower the production costs of therapeutic antibodies.